Finance and Development, June 1981. (Finance and Development; Finance and Development, 1981)
This paper highlights that the first quarter of 1981 was marked by a number of notable accomplishments in meeting the challenges currently facing the IMF. In addition to the completion of the final loan disbursements from the Trust Fund, the simplification of the SDR basket, and the decision to continue enlarged access to the IMF's resources, the IMF reached agreement in principle with Saudi Arabia on a quota increase and on an arrangement to borrow resources to permit the IMF to continue its lending operations without interruption and for the smooth functioning of the recycling process.